Evaluating benefits of patient-specific 3D-printed phantom designs in visceral surgery (Transactions on Additive Manufacturing Meets Medicine, 2022)
Scope of the presented study was to evaluate the suitability and usefulness of ten different 3D-printed patient-specific organ phantoms designs, created with varying additive manufacturing methods. 17 physicians of the Pius-Hospital; Oldenburg and the Gesundheit Nord (GeNo); Bremen were interrogated for their assessment of different organ phantoms designs within the framework of a formative evaluation. The participants preferred dyed phantoms with a scale of 50% of the original.
Keywords: visceral surgery; pre-operative planning; intra-operative planning organ phantom; patient-specific 3D-print; additive manufacturing; formative evaluation; planning- and educational models; SLS process; PA12 (Polyamide); TPU (thermoplastic polyurethane); Thinking-aloud method; LimeSurvey